PENGARUH MODEL PEMBELAJARAN QUANTUM TEACHING TERHADAP KEMAMPUAN MENULIS KARANGAN NARASI PADA SISWA SEKOLAH DASAR - Simanungkalit, Amelia; Purba, Nancy Angelia; Sidebang, Restio (Universitas Katolik Santo Thomas Medan, 2023)
The purpose of conducting this data was to determine the effect of the quantum teaching learning model on the ability to write narrative essays in class V of Bahbiak Siantar Adventist Private Elementary School. This research was carried out in the 2022/2023 school year. This research method is an experiment with a pre-experimental research design with a One-Group Pretest Post-test Design research design. The sample of this research is 33 students. Data collection techniques used are observation, documentation, and tests. Data is processed using statistical analysis techniques with the N-gain test. Based on the results of the hypothesis test, it was found that the ability to write narrative essays for fifth grade students had a normal with a final N-gain score of 0.52 in the moderate category. The pretest average score is 64.4 while the post-test average score is 83.5. The results of conceptual tests and problem solving strongly suggest that the use of the quantum teaching method in grade V can improve the effectiveness of students' narrative essay writing abilities in elementary schools.